Theoretical study of extended interaction frequency‐locking oscillator based on carbon nanotube cold cathodes. Issue 11 (24th July 2018) - Xie, Jie; Yuan, Xuesong; Chen, Qingyun; Yang, Tongbin; Zhang, Yu; Wang, Bin; Li, Hailong; Yan, Yang; Meng, Lin
Abstract : An extended interaction frequency‐locking oscillator based on carbon nanotube (CNT) cold cathode is proposed to overcome locked‐frequency limits of the conventional oscillator. Compared with the conventional oscillators, the oscillation frequency is locked by a modulation electron beam, which can be obtained in a field emission CNT cold cathode electron gun. The frequency‐locking signal does not enter the high‐frequency (HF) system but imposes an additional HF electric field on the cathode surface by a microstrip structure, which consumes considerably less power to lock the oscillation frequency. A ladder structure extended interaction oscillator operating in 2π mode is numerically investigated by three‐dimensional Particle‐In‐Cell simulation code. By analysing the impacts of different frequency‐locking power on the locked ranges, the results show that the average output power of 30.6 W is achieved at 35.11 GHz when the frequency‐locking power consumption is 460 mW. The 3‐dB bandwidth of a frequency‐locking region reaches 100 MHz.